Anúncios publicitários na escola: texto, prática discursiva e leitura(s) - Menezes, Ângela Maria de Araújo (2018)
The contemporary world establishes itself as an invitation to read. We see the present world not only through it, but also through the screens of electronics, posters, billboards, etc. This quick reading, which involves multiple semioses, requires the students to read proficiently. National and international assessments indicate weakness in the educational system and show that in reading, the brazilian student is in critical condition, many of them unable to overcome the understanding of textual superficiality. At this level, most of the students in the third step (eighth grade), class B, of Reference Center for Youth and Adult Education Prof. Severino Uchôa, state college located in the central area of Aracaju (SE). In order to lead students to a more conscious and critical reading, we prepared a proposal of intervention, from the genre of commercials. This proposal is based on three-dimensional model of Fairclough (2001), and on postulates of Critical Discourse Analysis (CDA), which sees the discourse as a linguistic, discursive and social practice. The conceptual metaphors, which are manifested in our discourses, are also present in this work, as a way of adding meaning to the reading of the genre in question. Our theoretical support was based on scholars such as Bakhtin (1992), Carvalho (2014), Pedrosa (2008), Lakoff & Johnson (2009), Marcuschi (2008), Freire (2016), Kleiman (2003), Foucambert (1994), Meurer (2014), Rojo (2009, 2012), Ramalho & Rezende (2011), among others. In this endeavor, we used the research-action methodology, having as object of research the action/reflection/action, in a construction of the teacher/student partnership. In the present research, of the 22 evaluated students, 17 presented a progress at reading of advertising texts, showing that working with a critical discursive perspective in reading is a way to be followed by education professionals who wish to broaden the reading awareness of their learners.